Komunikasi dalam Pengembangan Pasraman Sebagai Destinasi Pariwisata - Ni Kadek Karni; Ni Luh Senja Harining (Program Studi Magister S2 Ilmu Komunikasi Hindu Institut Agama Hindu Negeri Gde Pudja Mataram, 2022)
Pasraman, as a Hindu educational institution, has great potential to become a unique and attractive tourism destination, especially those based on religion and culture. However, the development of pasraman as a tourism destination requires the important role of effective communication. This article aims to explore the role of communication in the development of Pasraman as a tourism destination. Through a literature review and case studies, this research discusses the dynamics of communication involved in the process of developing pasraman as a tourism destination and the implications for tourism management and marketing. The research findings show that internal communication between acarya and brahmacari pasraman, as well as external communication between tourists and local communities, have an important role in building an authentic and sustainable tourism experience. In addition, the use of digital communication and social media also provides great opportunities in promoting and expanding the reach of pasraman as a tourism destination. The implications of this research underscore the importance of effective communication management in supporting the development of pasraman as a sustainable tourism destination and contributing to the preservation of Hindu culture. This article is expected to provide insight and practical guidance for managers and stakeholders in utilizing communication as the main tool in strengthening the role of Pasraman as an attractive and competitive tourism destination.